2009
DOI: 10.4049/jimmunol.0801811
|View full text |Cite
|
Sign up to set email alerts
|

Coronin 1 Is Essential for IgM-Mediated Ca2+ Mobilization in B Cells but Dispensable for the Generation of Immune Responses In Vivo

Abstract: Coronin 1 is a leukocyte specific regulator of Ca2+-dependent signaling and is essential for the survival of peripheral T lymphocytes, but its role in B cells is unknown. In this study, we show that coronin 1 is essential for intracellular Ca2+ mobilization and proliferation upon triggering of the BCR. However, the presence of costimulatory signals rendered coronin 1 dispensable for B cell signaling, consistent with the generation of normal immune responses against a variety of Ags in coronin 1-deficient mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
3
29
0
1
Order By: Relevance
“…This activation defect of naive T cells lacking coronin 1 is reflected by impaired proliferation and cytokine expression upon TCR stimulation in vitro. However, coronin 1-deficient mice are capable of mounting relatively normal Ab responses to T cell-independent, as well as T cell-dependent, Ags (24). The most striking effect of coronin 1 depletion is the apparent increased spontaneous apoptosis of naive T cells ex vivo (19,20,23).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This activation defect of naive T cells lacking coronin 1 is reflected by impaired proliferation and cytokine expression upon TCR stimulation in vitro. However, coronin 1-deficient mice are capable of mounting relatively normal Ab responses to T cell-independent, as well as T cell-dependent, Ags (24). The most striking effect of coronin 1 depletion is the apparent increased spontaneous apoptosis of naive T cells ex vivo (19,20,23).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, in the absence of coronin 1, MOG-specific T cell responses such as proliferation and cytokine expression after immunization with MOG peptide are delayed, as well as reduced, strongly suggesting a priming defect in the absence of coronin 1. In addition, several lines of evidence exclude a role for coronin 1 in Ag processing and presentation: 1) the restoration of EAE on transfer of wild-type T cells as shown in this study; 2) the absence of any defect in either macrophage, B cell, and dendritic cell function (3,24,25,38) and the absence of any gross defects in thymic selection, a process that is heavily dependent on Ag processing and presentation (19)(20)(21). Naive T cell priming, which is the initial step of an immune response, usually takes place in the draining lymph nodes where professional APCs activate naive T cells, leading to clonal expansion and differentiation into cytokine-expressing effector T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the phagocytic process of bacterial infection, p57/coronin-1 was shown to transiently accumulate on the surface of phagosomes and control the subsequent phagosome-lysosome fusion. Recent studies have also demonstrated that p57/coronin-1 was enriched in immunological synapses and involved in various immune regulatory functions such as signal transduction via T cell receptors (16 -18), survival of T cells (19,20), and intracellular Ca 2ϩ mobilization in T and B cells (19,21). More recently, it was reported that the p57/coronin-1 gene was responsible for human and mouse severe combined immunodeficiency (22,23).…”
mentioning
confidence: 99%